Quench deposited Kr-H2 and Ar-H2 mixtures: in quest of impurity-hydrogen gels - Strzhemechny, M.A.; Galtsov, N.N.; Prokhvatilov, A.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The structure and morphology of low-temperature quench condensed binary alloys of hydrogen with argon and krypton were studied by the powder x-ray diffraction. The nominal hydrogen fraction c in both systems was varied from 0 to 50%; the condensation was performed at 5-6 K; both as-prepared and annealed samples were examined by the x-ray diffraction. Few, often only one reflection can be unambiguously detected for the as-grown alloy samples. In the Kr-H2 condensates with c < 10%, the x-ray patterns show fine-grain krypton-rich crystallites with rather high actual hydrogen contents as estimated from Vegard`s law. At high nominal hydrogen fractions( %) c ≥ 10 ,no the reflections attributable to the krypton lattice were recorded and the incoherent background showed no characteristic swelling around the position of reflection (111) from pure Kr but, instead, the reflections from a hydrogen-rich hcp phase were distinct. As the temperature was steadily raised, first the hydrogen reflections disappeared and then, at a certain temperature, the samples underwent an abrupt transformation, releasing heat and making the krypton component forms larger, x-ray detectable textured crystallites. In the as-grown Ar-H2 samples, only (111) reflections from the argon-rich phase were recorded. Warmup led to the same consequences, viz., effusion of hydrogen and then recrystallization. In both systems, the recrystallization onset temperature depends substantially on the nominal hydrogen fraction in the gas. The shift of the lattice parameter in the as-grown argon-based phases suggests a strong suppression of the quantum nature of hydrogen in argon lattice environment. The entire set of the experimental findings can be treated as evidence that the quench-condensed hydrogen-containing alloys morphologically resemble helium-impurity solids (gels) whose structure and morphology are currently studied at Cornell University.